Marketing Mix is The Only Variable to Choose Brands and Quality? - Krisnanto, Umbas (Universitas Prasetiya Mulya, 2013)
This research is to find out how the role and influence of marketing stimuli (advertising, pricing, and sales promotion) as well as the role of family and brand awareness, brand associations, perceived quality of Pepsodent toothpaste. The benefits of this research study is expected to be considered in developing a marketing mix that ultimately led to the formation of perceived qualitys. Second, updating the theory of consumer behavior and marketing theory. This research method is accomplished by using a descriptive study using survey. The population in this study is consumer of Pepsodent toothpaste. Samples done by accidental sampling. For data collection questionnaire used closed type. Operationalization variable using descriptive and quantitative analysis variable (GSCA and SEM). The results showed the influence of very low ranging from 0.00 to 0.19 for the relationship of advertising and brand awareness variables, the price and brand association variables, promotion and brand awareness variables, relationship between family variable and brand awareness and brand association. While family variable and perceived quality variable had reverse effect. The low but definite effect ranged from 0.20 to 0.39 for the advertising variable, brand associations variable, and perceived quality as well as variable promotion, promotional variable to variable brand associations and perceived quality variables. The effect was ranged from 0.40 to 0.60 for brand awareness and perceived quality variables. Recommendations to PT Unilever should deliver more competitive promotion thus proving that good quality is always supported by good and great promotion, low price version. Pepsodent should promote impressed with quality, still showing the previous experience of the people who have benefited from Pepsodent, while providing marketing and advertising top of mind to their customers so that they lose sight of the Pepsodent, still suggested best quality can be compared with its competitors, the evidence suggests that the quality is always the best.